Anti-HBs prevalence and assessment of the response to serological Hepatitis B vaccine in patients eligible for liver transplantation at Hospital Santa Isabel of Blumenau/Santa Catarina - Nogara, Marcelo Augusto Scheidemantel; Perini, Luiza Dadan; Salles, Fabiane Miura Ogg De; Noronha, Maria Gabriela Ortiz de; Seter, Guilherme Bortolli; Batista, Camila Ribeiro (Brazilian Journal of Transplantation, 2014)
Purpose: Anti-HBs positive is a protective factor for patients eligible for liver transplantation, as it poses immunity against the hepatitis B virus (HBV). After three doses of the vaccine more than 90% of young adults develop adequate Anti-HBs antibody responses. The aims of this study were to identify the prevalence of anti-HBs and assess the antibody response to hepatitis B vaccine in patients eligible for liver transplantation at Hospital Santa Isabel of Blumenau/ SC. Methods: This study was conducted in two steps during the period between March 2011 and July 2012, at Hospital Santa Isabel in Blumenau / SC. The first step was an observational cross-sectional study based on medical chart review. The population consisted of all patients eligible for liver transplantation who remained on the list until March 16, 2011. The clinical variables studied were: age, gender, origin, presence of anti-HBs, presence of anti-HBc and presence of HBsAg, MELD score. The second step was a longitudinal study, composed by patients who were susceptible in the first stage of the study. The variables studied were: presence of Hepatitis B vaccination, amount of doses of the hepatitis B vaccine, presence of after vaccination anti-HBs positive, Child-Turcotte-Pugh classification and MELD score. Results: We reviewed 150 medical charts of all patients eligible for liver transplantation. The mean age was 53.2 years, and 64% of the studied population were male. The prevalence of anti-HBs positive was 14.64%, showing no significant relationship both with the MELD score and the Child-Turcotte-Pugh classification. Regarding the seroconversion, 21.4% of patients seroconverted after at least one dose of the vaccine against hepatitis B. Conclusion: There was low prevalence of anti-HBs positive in patients eligible for liver transplantation. The literature shows that the vaccine seroconversion is higher than data found in this study; however, it is based on surveys of the general population. Vaccination in patients eligible for liver transplantation should be recommended, as the seroconversion of those patients provides protection against infection by hepatitis B. Further studies are required to compare the prevalence of anti-HBs seroconversion after vaccination and such marker in patients eligible for liver transplantation.